Optimization Of Cogging Torque in 28-Pole 24-Slot Permanent Magnet Generator - Zacky Irfan Al Farisie; Tajuddin Nur; Marwan Rosyadi; Syamsir Abduh (Green Publisher Indonesia, 2026)
This study addresses the growing demand for efficient renewable energy conversion systems, particularly in low- to medium-wind-speed regions such as Indonesia, where wind resources typically range between 4–6 m/s. Permanent magnet generators (PMGs) are widely used in wind power plants due to their high efficiency and simple structure; however, their performance is often limited by cogging torque, which causes rotational resistance, vibration, and reduced energy conversion efficiency. This research aims to analyze and optimize the reduction of cogging torque in a 28-pole, 24-slot permanent magnet generator through geometric modification techniques. The study employs a quantitative simulation approach using FEMM 4.2 software and LUA 4.0 scripting to model magnetic flux distribution and torque characteristics. The optimization process includes variations in air gap widening, magnet edge shaping, slot opening adjustment, and the addition of dummy slots. The initial design produced a cogging torque of 0.00498 Nm. After the first optimization stage, the value decreased to 0.00028 Nm, while the second optimization achieved a significant reduction to 0.00005 Nm, corresponding to a 98.99% decrease. The results demonstrate that combining magnet edge shaping with dummy slots is highly effective in minimizing cogging torque and improving flux uniformity. In conclusion, the optimized design enhances generator performance, particularly in low-speed wind applications, making it a promising solution for sustainable energy development.